E. Husserl: Specific Features of Phenomenology and the Structure of the Investigation of Time - Mickevičius, Arūnas (Problemos, 1996)
E. Husserl’s investigation of time is based on the description of peculiarities of perception and of perceptible objects. He is talking about temporal phenomenon, time consciousness (Zeitbewusstsein), continuity of temporal phases, theories of time (F. Brentano, J. F. Herbart, H Lotze). E Husserl applies in his investigations special notions and also notions of perception, memory and fantasy which are modes of consciousness and forms of time expression.